Co-occurring congeners coordinate drought and shade tolerance traits along gradients of canopy openness - Sam W. Anderson; Jackson Cramer; Katherine A. McCulloh (Oecologia, 2026)
Physiological traits related to water status and photosynthesis biophysically link plant performance to environmental conditions like light and water availability. By approaching the concept of species’ niches from a trait-based perspective, physiological traits can be used to characterize how trait syndromes diverge to limit direct resource competition and promote resource partitioning in sympatric species. Such traits could also inform broader studies of changing community composition in an era of drastic shifts in climate or disturbance regimes. However, the extent of inter/intraspecies trait variation and how such traits vary along local environmental gradients remains an open question in understanding physiological traits as species-level characteristics. To address this, we quantified hydraulic and gas exchange traits in four co-occurring Viburnum species while also quantifying local canopy coverage and soil conditions. All species displayed significant variation in gas-exchange traits, turgor loss point, and heavy carbon isotope discrimination along gradients of canopy openness. Specifically, plants in shadier environments exhibited higher photosynthetic rates at low light levels while individuals growing in gaps demonstrated higher drought tolerance and stricter stomatal regulation. Soil texture explained little variation in traits assessed. V. acerifolium displayed a more conservative, shade-tolerant trait syndrome, yet little significant difference was found in traits between the congeners, highlighting the potentially limited resolution of physiological traits to differentiate trait syndromes of closely related, co-occurring species.

Why primatology needs local knowledge - Sam Adue; Walter Akankwasa; Jackson Asua; Gideon Atyo; Bosco Chandia; Noémie Freymond; Vicent Kizza; Harmonie Klein; Monday M’Botella; Stephen Mugisha; Geresomu Muhumuza; Mike Matthew Musiimenta; et al. (Primates, 2026)

Maximum nutrition, minimum waste – exploring attitudes and behaviours towards food waste and ‘root-to-tip’ dining within the home - Georgia Browne; Fiona Lavelle; Gillian Brooks; Fatima Wang; Balazs Bajka; Peter Ellis; Graeme Collie; Eric Wu; Sam Jackson; Rachel Gibson (Appetite, 2025)

Microplastic pollution on historic facades: Hidden ‘sink' or urban threat? - Katrin Wilhelm; Sam Woor; Michelle Jackson; Dania Albini; Neil Young; Phani Karamched; Miriam C. Policarpo Wright; Josep Grau-Bove; Scott Allan Orr; Jack Longman; Tim de Kock (Environmental Pollution, 2024)

Whole genome analyses reveal weak signatures of population structure and environmentally associated local adaptation in an important North American pollinator, the bumble bee Bombus vosnesenskii - Sam D. Heraghty; Jason M. Jackson; Jeffrey D. Lozier (Molecular Ecology, 2023)
Studies of species that experience environmental heterogeneity across their distributions have become an important tool for understanding mechanisms of adaptation and predicting responses to climate change. We examine population structure, demographic history and environmentally associated genomic variation in Bombus vosnesenskii , a common bumble bee in the western USA, using whole genome resequencing of populations distributed across a broad range of latitudes and elevations. We find that B. vosnesenskii exhibits minimal population structure and weak isolation by distance, confirming results from previous studies using other molecular marker types. Similarly, demographic analyses with Sequentially Markovian Coalescent models suggest that minimal population structure may have persisted since the last interglacial period, with genomes from different parts of the species range showing similar historical effective population size trajectories and relatively small fluctuations through time. Redundancy analysis revealed a small amount of genomic variation explained by bioclimatic variables. Environmental association analysis with latent factor mixed modelling (LFMM2) identified few outlier loci that were sparsely distributed throughout the genome and although a few putative signatures of selective sweeps were identified, none encompassed particularly large numbers of loci. Some outlier loci were in genes with known regulatory relationships, suggesting the possibility of weak selection, although compared with other species examined with similar approaches, evidence for extensive local adaptation signatures in the genome was relatively weak. Overall, results indicate B. vosnesenskii is an example of a generalist with a high degree of flexibility in its environmental requirements that may ultimately benefit the species under periods of climate change.

Dead-infant carrying by chimpanzee mothers in the Budongo Forest - Adrian Soldati; Pawel Fedurek; Catherine Crockford; Sam Adue; John Walter Akankwasa; Caroline Asiimwe; Jackson Asua; Gideon Atayo; Boscou Chandia; Elodie Freymann; Caroline Fryns; Geresomu Muhumuza; et al. (Primates, 2022)
It has been suggested that non-human primates can respond to deceased conspecifics in ways that suggest they experience psychological states not unlike humans, some of which could indicate they exhibit a notion of death. Here, we report long-term demographic data from two East African chimpanzee groups. During a combined 40-year observation period, we recorded 191 births of which 68 died in infancy, mostly within the first year. We documented the post-mortem behaviour of the mothers and describe nine occasions where Budongo chimpanzee mothers carried infants for 1–3 days after their death, usually until the body started to decompose. We also observed three additional cases of extended carrying lasting for more than 2 weeks, one of which was followed by the unusual extended carrying of an object and another which lasted 3 months. In each case, the corpses mummified. In addition, we report four instances of recurring dead-infant carrying by mothers, three of whom carried the corpse for longer during the second instance. We discuss these observations in view of functional hypotheses of dead-infant carrying in primates and the potential proximate mechanisms involved in this behaviour.

Occurrence of pathogens in Pacific lamprey (Entosphenus tridentatus) - Aaron D. Jackson; Mary L. Moser; Sam T. Onjukka; Scott LaPatra; Kenneth M. Lujan; Corie Samson; Melissa G. White; Marilyn Blair; Linda Rhodes; Ralph Lampman; Alexa N. Maine; Jeffrey C. Jolley (Reviews in Fish Biology and Fisheries, 2019)

Intragroup competition predicts individual foraging specialisation in a group‐living mammal - Catherine E. Sheppard; Richard Inger; Robbie A. McDonald; Sam Barker; Andrew L. Jackson; Faye J. Thompson; Emma I. K. Vitikainen; Michael A. Cant; Harry H. Marshall (Ecology Letters, 2018)
Individual foraging specialisation has important ecological implications, but its causes in group‐living species are unclear. One of the major consequences of group living is increased intragroup competition for resources. Foraging theory predicts that with increased competition, individuals should add new prey items to their diet, widening their foraging niche (‘optimal foraging hypothesis’). However, classic competition theory suggests the opposite: that increased competition leads to niche partitioning and greater individual foraging specialisation (‘niche partitioning hypothesis’). We tested these opposing predictions in wild, group‐living banded mongooses ( Mungos mungo ), using stable isotope analysis of banded mongoose whiskers to quantify individual and group foraging niche. Individual foraging niche size declined with increasing group size, despite all groups having a similar overall niche size. Our findings support the prediction that competition promotes niche partitioning within social groups and suggest that individual foraging specialisation may play an important role in the formation of stable social groupings.

Autonomous CTD Profiling from the Robotic Oceanographic Surface Sampler - Jonathan Nash; June Marion; Nick McComb; Jasmine Nahorniak; Rebecca Jackson; Corwin Perren; Dylan Winters; Andy Pickering; Jorian Bruslind; Onn Lim Yong; Sam Lee (Oceanography, 2017)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.